1991
DOI: 10.1042/bj2730085
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the RTEM-1 cysteine β-lactamase by iodoacetate. The nature of active-site functional groups and comparisons with the native enzyme

Abstract: The pH-rate profile for inactivation of the RTEM-1 cysteine beta-lactamase by iodoacetate supports previous evidence [Knap & Pratt (1989) Proteins Struct. Funct. Genet. 6, 316-323] for the activation of the active-site thiol group by adjacent functional groups. The enhanced reactivity of iodoacetate, with respect to that of iodoacetamide, suggests the influence of a positive charge in the active site. The reactivity of iodoacetate is not affected by dissociation of an active-site functional group of pKa 6.7, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…These compounds are well known enzyme inhibitors specific for certain enzymes. PMSF is a serine protease inhibitor, IAA a cysteine peptidase inhibitor, while EDTA is a metallopeptidase inhibitor . Sodium azide is a known nitrate reductase inhibitor .…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are well known enzyme inhibitors specific for certain enzymes. PMSF is a serine protease inhibitor, IAA a cysteine peptidase inhibitor, while EDTA is a metallopeptidase inhibitor . Sodium azide is a known nitrate reductase inhibitor .…”
Section: Resultsmentioning
confidence: 99%
“…Although 3 and 4 are not as effective as inhibitors of the class A ,-lactamases, as is 2 of the class C P99 enzyme [7], the most interesting result here, as there, is that they are inhibitors at all, and particularly by a mechanism involving phosphonate cleavage. This suggests that the fi-lactamase active site, in contrast with the serine-proteinase active site [12], is able to stabilize very effectively a transition state resembling 5. The /3-lactamase active site is characterized by the presence of much positive charge [13][14][15], which may be employed to stabilize the transition states of RCONH \ Nuc8+---P --8-OAr a0 0 5 normal substrates [12] and of phosphonate monoesters (6); in 6, the numbering system of Ambler [3] is employed, and the general-base role of Glu-166 is speculative [12].…”
Section: Resultsmentioning
confidence: 99%
“…For LPase to utilize this mechanism would require an active site lysine possessing a pKa below 5 as there are no ionizations observed over the pH range studied in this work. In fact, Knap and Pratt (1991) have argued that the group which displays a pKa of 7.5 in the class A /3-lactamase reactions is actually Lys-234 and not Lys-73. Lys-234 is thought to interact with the lo During review it was suggested that interpretation of the pH profiles is complicated by lack of information concerning, the product ratio as a function of pH.…”
Section: 1994mentioning
confidence: 97%